ANALISIS POLA USAHATANI KAKAO TUMPANGSARI DENGAN TANAMAN TAHUNAN DI KABUPATEN KOLAKA - , Kabul Budiman, Dr.Ir. Slamet Hartono,SU.,M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aimed to analyze the factors that affect farmers in the choice of cropping patterns, analyze the financial feasibility, determine the factors that influence the production, to know the factors that affect revenue, to know the level of technical, allocative, and economic efficiency, to know distribution of income at various patterns of intercropping-cocoa farming with perennials plant. Determination of the sample to be the object of this study was on Kolaka consisting of 17 districts drawn from three purposively District. Each district was represented 3 villages purposively. Each district was taken 9 villages with a random sample number 270. The analysis used were multinomial logit analysis, analysis of production and income, multiple linear regression with OLS (Ordinary Least Square) method, the analysis of frontier production functions, technical, economic and allocative efficiency analysis with frontier, and the Gini Ratio. Result of the research indicated that: Factors affecting farmers in the selection of the cropping pattern with intercropping-cocoa farming in positive were: the number of family members, guidance of field informer (PPL), age of farmers, farmer experiences, successes of other farmers and land positions. Intercropping cocoa farm using KKN indicated that the value of R/C ratio, B/C ratio, NPV, IRR and payback period were more viable than KKJ and KKP patterns. Factors of production including arable land, labor, manure, fertilizer urea, fertilizer SP36, KCL fertilizer, insecticide, education, and experience had a positive effect on production, while herbicide, age of farmers, the number of staple crops, staple plant age, success of other farmers, domestic growers, cropping patterns, land position had a negative effect on production. Factors including another successful farmer, a farmer from Celebes, Javanese farmers, land position, and Pol Planting and variable